Effective Evaluation of the Noise Factor of Microchannel Plate. (26th August 2015) - Wang, Honggang; Du, Yujie; Feng, Yu; Lv, Yang; Hu, Xiaoming; Qian, Yunsheng
Abstract : To improve the noise performance of microchannel plate (MCP), we have presented a method using the sine random signals with Poisson distribution as the noise-excitation for electron source. By using this method, the effective evaluation of noise characteristics of MCP has been implemented through measuring and analyzing its noise factor. The results have demonstrated that the noise factor of filmed MCP is lower than 1.8. Additionally, as the open area ratio and the input electron energy are 72% and 400 eV, respectively, the noise characteristics of unfilmed MCP are improved evidently. Moreover, larger open area ratio, higher input electron energy, and higher voltage across the MCP all can reduce effectively the noise factor within a certain range. Meanwhile, the ion barrier film extends the life of image tube but at the cost of an increased noise factor. Therefore, it is necessary that a compromise between the optimum thickness of ion barrier film, open area ratio, input electron energy, and voltage across the MCP must be reached.